Buletin Peternakan : Pengaruh Tepung Daun Sirsak (Announa Muricata L) terhadap Karakteristik Lemak Darah dan Daging Itik Tegal Jantan - Elly Tugiyanti, Soegeng Heriyanto, Afduha Nurus Syamsi (Peternakan UGM, 2016)
The purpose of this experiment was to evaluate the effect of soursop leaf meal on characteristics of blood and meat fat of male Tegal ducks. This study used completely randomized design.